Combining genomics and epidemiology to investigate a zoonotic outbreak of rabies in Romblon Province, Philippines - Mirava Yuson; Criselda T. Bautista; Eleanor M. Rees; Carlijn Bogaardt; Van Denn D. Cruz; Rowan Durrant; Anna Formstone; Daria L. Manalo; Duane R. Manzanilla; Mikolaj Kundergorski; Leilanie Nacion; Hannaniah Aloyon; et al. (Nature Communications)
Abstract Rabies is a viral zoonosis that kills thousands of people annually in low- and middle-income countries across Africa and Asia where domestic dogs are the reservoir. ‘Zero by 30’, the global strategy to end dog-mediated human rabies, promotes a One Health approach underpinned by mass dog vaccination, post-exposure vaccination of bite victims, robust surveillance and community engagement. Using Integrated Bite Case Management (IBCM) and whole genome sequencing (WGS), we enhanced rabies surveillance to detect an outbreak in a formerly rabies-free island province in the Philippines. We inferred that the outbreak was seeded by at least three independent human-mediated introductions that were identified as coming from neighbouring rabies-endemic provinces. Considerable local transmission went undetected, and two human deaths occurred within 6 months of outbreak detection. Suspension of routine dog vaccination due to COVID-19 restrictions likely facilitated rabies spread from these introductions. Emergency response, consisting of awareness measures, and ring vaccination, were performed, but swifter and more widespread implementation is needed to contain and eliminate the outbreak and to secure rabies freedom. We conclude that strengthened surveillance making use of new tools such as IBCM, WGS, and rapid diagnostic tests can support One Health in action and progress towards the ‘Zero by 30’ goal.